Liquid Soap Formulation Ethanol Extract Avocado Skin (Persea americana) Against Bacteria Staphylococcus aureus - Suryani, Ade Irma; Ambarsari, Niati; Oktaviani, Milla; Rerung, Lola’ Tulak; Sari, Rahayu Mustika; Kemal, Amir; Dewi, Hasna (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
Avocado peels contain Flavonoid compounds and alkaloids as antibacterial. In this study, the ethanol extract of Avocado peels was formulated as a liquid soap using concentrations of FI (1%), FII (3%) and FIII (5%). This study aimed to formulate a liquid soap from a sample of Avocado peel extract against the antibacterial activity ofStaphylococcus aureususing the agar diffusion method in wells. Physical evaluation of liquid soap preparations includes several parameters, namely organoleptic tests including odour, shape and colour, pH test, foam stability test, viscosity test and homogeneity test. The results obtained from testing liquid soap using ethanol extract of Avocado peels with varying concentrations of 1%, 3% and 5% can inhibit the growth of Staphylococcus aureus bacteria, namely 1% = 19.6, 3% = 21.6 and 5% = 25.8. Based on the results of this study it can be concluded that the ethanol extract of Avocado peels (Persea americana) can be formulated in the form of liquid soap and is effective against inhibition of Staphylococcus aureus bacteria. In this study, FIII fulfilled the physical quality evaluation test and had activity as an antibacterial, with the resulting inhibition zone at a concentration of 5% = 26.6 mm, a powerful category.